Electrical safety in educational and work environments: a regional análisis - Taguada , Dennise; Quimiz , Ana; Pizaña , Anderson; Ortiz , Kerly (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
The research analyzed electrical hazards in Latin America, highlighting their impact on educational and work environments. In Ecuador and Colombia, studies showed that lack of maintenance, improper handling of equipment and lack of technical training significantly increased electrical accidents. Cazallas Suárez and Gámez Gómez (2021) identified in Colombia the consequences of these risks in buildings constructed before the Technical Regulations for Electrical Installations (RETIE), highlighting effects such as irreversible damage and mortality.In Ecuador, a research by Correa Iván Marcelo (2020) pointed out that the use of equipment without technical knowledge increased the risks in educational institutions. In the Atahualpa Educational Unit, in Ambato, deficiencies in electrical safety were evidenced, such as lack of signaling, absence of protocols and use of low quality materials, exposing students and teachers to considerable dangers.In 2022, these issues became more relevant due to the inequalities aggravated by the pandemic and the growing use of electrical technologies. The International Labor Organization promoted safety measures, but their implementation faced financial barriers. The research highlighted the importance of clear protocols, constant training and a culture of safety. It also emphasized the role of parents and authorities in ensuring safe facilities and adequate resources.In conclusion, it highlighted the need for a comprehensive approach that combines education, regulation and investment in infrastructure to prevent electrical accidents, ensure well-being and promote sustainable development in the region